2011
DOI: 10.5586/asbp.2005.040
|View full text |Cite
|
Sign up to set email alerts
|

Pollen morphology of the Polish species of the genus Sorbus L.

Abstract: This paper presents the results of the study on pollen morphology of five Polish species of the genus Sorbus L. (S. aria (L.) Crantz, S. aucuparia L. Emend. Hedl., S. chamaemespilus (L.) Crantz, S. intermedia (Ehrh.) Pers. and S. torminalis (L.) Crantz). Observations were carried out with light and scanning microscopes. Investigated pollen grains were small or medium size, most often subprolate or prolate spheroidal in outline. Exine of medium thickness, consisted of two layers. Mainly 3-zonocolporate or somet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 5 publications
1
22
0
Order By: Relevance
“…A comparative study on pollen morphology of Prunoideae of China has been investigated by Zhou et al (1999). Several other researchers studied the pollen morphology of rosaceous members including Reitsma (1967), Ueda and Tomita (1989), Hebda and Chinnappa (1990a, b), Bednorz et al (2005) and Dönmez (2008). Present research is the first study on pollen grain morphology of Iranian species of Amygdalus.…”
Section: Introductionmentioning
confidence: 87%
“…A comparative study on pollen morphology of Prunoideae of China has been investigated by Zhou et al (1999). Several other researchers studied the pollen morphology of rosaceous members including Reitsma (1967), Ueda and Tomita (1989), Hebda and Chinnappa (1990a, b), Bednorz et al (2005) and Dönmez (2008). Present research is the first study on pollen grain morphology of Iranian species of Amygdalus.…”
Section: Introductionmentioning
confidence: 87%
“…Pollen grains are elliptic, 22–40 μm in diameter, 3(4)‐colporate, and of medium size compared to other species within the genus (Bednorz et al . ). Pollen viability is affected by both temperature and humidity (Termena ) and was found by Price & Rich () to vary around England between 50 and 100%, with a mean of 75%.…”
Section: Floral and Seed Charactersmentioning
confidence: 97%
“…They thought the pollen size to be the least reliable feature and they related it to the comparatively frequent occurrence of hybrid and polyploid species in this family. In the subgenera Sorbus, Chamaespilus and Torminaria belonging to the genus Sorbus, pollen morphology corresponds with their systematic classification [16], while in the genus Rosa, a recent study showed that the exine sculpture can be helpful in distinguishing groups of species although only slightly corroborates division of the genus in subgenera and sections [17].…”
Section: Introductionmentioning
confidence: 99%